Low-temperature energy systems with applications of renewable energy - Redko, Andriy; Redko, Oleksandr; DiPippo, Ronald (Academic Press, an imprint of Elsevier, 2020)
Low-Temperature Energy Systems with Applications of Renewable Energy investigates a wide variety of low-temperature energy applications in residential, commercial, institutional, and industrial areas. It addresses the basic principles that form the groundwork for more efficient energy conversion processes and includes detailed practical methods for carrying out these critical processes. This work considers new directions in the engineering use of technical thermodynamics and energy, including more in-depth studies of the use of renewable sources, and includes worked numerical examples, review questions, and practice problems to allow readers to test their own comprehension of the material. With detailed explanations, methods, models, and algorithms, Low-Temperature Energy Systems with Applications of Renewable Energy is a valuable reference for engineers and scientists in the field of renewable energy, as well as energy researchers and academics. --